The Iberian Pork Meat Industry in Jabugo (Huelva, Spain), 1997-2016. - García-Delgado, Francisco Javier; Domínguez-Santos, Daniel; Pizarro-Gómez, Antonio (Revista de Estudios Andaluces, 2017)
The municipality of Jabugo is one of the most important in the transformation of the Iberian pork. In the last decades, the industry has undergone a transformation, with processes of concentration, relocation and positioning among the companies in the industry. As a result, large companies have been strengthened, and the Protected Designation of Origin “Jabugo" emerges as an opportunity for the sector.